THE INHIBITORY POWER OF PINEAPPLE HUMP ETHANOL EXTRACT TOWARD THE GROWTH OF STREPTOCOCCUS MUTANS - Minarni Minarni (JDHT Journal of Dental Hygiene and Therapy, 2023)
Background:This study aimed to investigate inhibitory powers of etanol extract from pinnaple hump with concentrations of 7,5%, 10%, 15%,  20%, 25%, and 30% toward the growth of  Streptococcus mutans bacteria. Methods: Pineapple hump extract was made using maseration technique with ethanol 96% as a solvent. Agar well diffusion method was used in order to investigate the inhibitory ability of pineapple humpagainst Streptococcus mutans. Few (20-100 µl) volume of the pineapple hump extract solution from each of concentrations was placed into each of well on blood agar in petri dishes had contained Streptococcus mutans then incubated for 24 hours at 370C temperature, lastly the measurement of inhibition power was measured with caliper. Results: The results showed that pineapple hump extract with concentrations of 7,5%, 10%, 15%, 20%, 25%, and 30% could inhibit the growth of Streptococcus mutans bacteria. Pineapple hump extracts with concentrations of 7,5% and 10% have moderate inhibition power (average diameter respectively are 7,45 mm and 8,58 mm), pineapple hump extracts with concentrations of 15%, 20%, 25%, and 30% have strong inhibition power (average diameter respectively are 10,16 mm, 11,33 mm, 13,33 mm, and 14,83 mm). Conclusions: The Conclusion is: ethanol extract of pineapple hump has inhibitory power toward the growth of Streptococcus mutans within range of moderate category and strong category